2014
DOI: 10.1038/aps.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Lapatinib-incorporated lipoprotein-like nanoparticles: preparation and a proposed breast cancer-targeting mechanism

Abstract: Aim: Lapatinib is a dual inhibitor of EGFR and human epidermal growth factor receptor 2 (HER2), and used to treat advanced breast cancer. To overcome its poor water solubility, we constructed lapatinib-incorporated lipoprotein-like nanoparticles (LTNPs), and evaluated the particle characteristics and possible anti-breast cancer mechanisms. Methods: LTNPs (lapatinib bound to albumin as a core, and egg yolk lecithin forming a lipid corona) were prepared. The particle characteristics were investigated using trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Micron size particles are generally known to internalize the cells via macropinocytosis [83], however; most of the literature reports highlight that the nanoparticles undergo cellular internalization via more than one endocytic pathway. Recently, Zhang et al [84] reported lapatinib loaded nanoparticles formulated with a core of albumin and a lipid corona formed by the egg yolk lecithin. The nanoparticles exhibited ~62 nm and a zeta potential of 22.80 mV and were demonstrated to internalize the BT-474 cells through energy-dependent endocytosis involving clathrin-dependent pinocytosis and macropinocytosis.…”
Section: Endocytic Routes and Non-ligand Targeted Nanomedicinesmentioning
confidence: 99%
“…Micron size particles are generally known to internalize the cells via macropinocytosis [83], however; most of the literature reports highlight that the nanoparticles undergo cellular internalization via more than one endocytic pathway. Recently, Zhang et al [84] reported lapatinib loaded nanoparticles formulated with a core of albumin and a lipid corona formed by the egg yolk lecithin. The nanoparticles exhibited ~62 nm and a zeta potential of 22.80 mV and were demonstrated to internalize the BT-474 cells through energy-dependent endocytosis involving clathrin-dependent pinocytosis and macropinocytosis.…”
Section: Endocytic Routes and Non-ligand Targeted Nanomedicinesmentioning
confidence: 99%
“…Lapatinib is poorly soluble in water, but after being encapsulated in lipoproteins to form nanoparticles (LTNPs), its water solubility increases from 7 μg/mL to 10 mg/mL or more. AFM measurements showed that LTNPs are spherical particles, and that the height of the particles is not positively correlated with the diameter, as the diameter is about 60 nm and the height is less than 3 nm [ 118 ].…”
Section: Evaluation and Development Of Antitumor Drugsmentioning
confidence: 99%
“…Currently, chemotherapy is one of the most important treatment strategies for metastatic cancer, but its therapeutic effect is impaired by toxic effects on both cancer cells and normal cells [7,8] . Fortunately, nanodrug delivery systems can break through various biological barriers by taking advantage of the enhanced penetration and retention (EPR) effects of solid tumors [9][10][11][12][13] to increase the intra-tumoral accumulation of drugs, reduce the side effects of chemotherapy [3,[14][15][16][17][18] and potentially inhibit metastatic breast cancer.…”
Section: Introductionmentioning
confidence: 99%